Equivalences in Variations of Selection Principles with Particular Classes of Families of Subsets of a Topological Space $X$X - Fernández, Juan (Topology Proceedings, 2025)
We present some results about the equivalences between the different variations in selection principles in certain types of classes of subsets of topological spaces, and we revisit particular cases.